Pilsen, Red Ale and Stout brewer’s spent grain: polyphenols, antioxidant and antihypertensive activities, and physicochemical properties - Bagatini, Lisangela; Veras, Flávio Fonceca; Azevedo, Gabriela Diersmann; Sant Anna, Voltaire; Brandelli, Adriano (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
The objective of this work was to evaluate the concentration of phenolic compounds, the antioxidant and anti-hypertensive capacity, and the physicochemical characteristics of brewer’s spent grain (BSG) from Pilsen, Red Ale and Stout beers. Results indicate that the studied byproducts present high concentration of total polyphenols, flavonols and phenolic acids. The evaluation of antioxidant potential revealed up to 60.9% scavenging of ABTS radicals, 12.3% of DPPH radicals and 12.4% of iron chelating power. In addition, 64.6% inhibition of angiotensin-I-converting enzyme was observed, suggesting anti-hypertensive capacity. Results of water and oil absorption capacity indicates that BSG powders presents similar values to cereal flours. CIELab values show that Pilsen BSG present light-yellow color, meanwhile Red Ale and Stout preferably dark color. The BSG powder presents pH values lower than 5.0, indicating acid conditions, which may contribute to bacterial stability for medium to long term storage of the dried residues. The present work shows that the BSG can be an alternative source of functional compounds, representing a sustainable way of industrial waste management.